Dual-Color Live Imaging of Adult Muscle Stem Cells in the Embryonic Tissues of Drosophila melanogaster. - Zmojdzian, M.; Dhanarajan, B.; Jagla, K.; Aradhya, R. (Bio-protocol, 2023)
Adult muscle stem cells (MuSCs) show remarkable capability in repairing injured tissues. Studying MuSCs in suitable model organisms, which show strong homology with vertebrate counterparts, helps in dissecting the mechanisms regulating their behavior. Additionally, ease of handling and access to technological tools make model organisms well suited for studying biological processes that are conserved across species. MuSCs quiescence, proliferation, and migration are regulated by various input of signals from the surrounding tissues that constitute the MuSCs niche. Observing MuSCs along with their niche in vivo through live imaging provides key information on how MuSCs behave in quiescent and activated states. Drosophila melanogaster is well known for its genetic tool arsenal and the similarity of its different biological processes with vertebrates. Hence, it is widely used to study different types of stem cells. Gained knowledge could then be extrapolated to the vertebrate/mammalian homologous systems to enhance our knowledge in stem cell fields. In this protocol, we discuss how to perform live cell imaging of Drosophila MuSCs, called adult muscle precursors (AMPs) at embryonic stages, using dual-color labelling to visualize both AMPs and the surrounding tissues. This dual-color fluorescent labelling enables the observation of in vivo behavior of two types of cells simultaneously and provides key information on their interactions. The originality of this protocol resides in its biological application to MuSCs and their niche.